A new test specimen to investigate the bond behavior of post‐installed reinforcing bars. (20th December 2018) - Rex, Justus; Sharma, Akanshu; Hofmann, Jan
Abstract : Recent developments in the field of adhesives have led to the availability of post‐installed reinforcing bar (rebar) systems with high strength mortar. The bond strength of these mortar‐rebar systems can reach significantly higher values than the bond strength of cast‐in rebar systems in normal strength concrete. However, based on the boundary conditions of concrete cover, concrete strength, transverse reinforcement, etc., the usable bond strength of post‐installed rebar system could be limited by concrete splitting prior to attainment of the bond strength. In order to study the influence of above‐stated boundary conditions on the usable bond strength of post‐installed rebar, a new test specimen is designed on the basis of the beam‐end specimen. The specimen allows for testing of the post‐installed rebar system under realistic boundary conditions and clearly defined bonded zone while measuring unloaded‐end slip and the width of splitting cracks.